Impact of COVID-19 outbreak on clinical practice and training of young gastroenterologists: A European survey - Marasco, Giovanni (Dig Liver Dis, 2020)
BACKGROUND: SARS-CoV-2 disease (COVID-19) is a major challenge for the healthcare system and physicians, imposing changes in daily clinical activity. AIMS: we aimed to describe what European trainees and young gastroenterologists know about COVID-19 and identify training gaps to implement educational programs. METHODS: A prospective web-based electronic survey was developed and distributed via e-mail to all members of the Italian Young Gastroenterologist and Endoscopist Association and to European representatives. RESULTS: One hundred and ninety-seven subjects participated in the survey, of whom 14 (7.1%) were excluded. The majority were gastroenterologists in training (123, 67.7%) working in institutions with COVID-19 inpatients (159, 86.9%), aged ≤30 years (113, 61.8%). The activity of Gastroenterology Units was restricted to emergency visits and endoscopy, with reductions of activities of up to 90%. 84.5% of participants felt that the COVID-19 outbreak impacted on their training, due to unavailability of mentors (52.6%) and interruption of trainee's involvement (66.4%). Most participants referred absence of training on the use of personal protective equipment, oxygen ventilation systems and COVID-19 therapies. CONCLUSION: COVID-19 outbreak significantly impacted on gastroenterologists’ clinical activity. The resources currently deployed are inadequate, and therefore educational interventions to address this gap are warranted in the next future.